An Architecture with Support Semantic for Discovery Resources in Ubiquitous Computing - Dilli, Renato; Venecian, Luthiano; Rodrigues, Sergio; Yamin, Adenauer; Warken, Nelsi (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2010: Anais do XI Simpósio em Sistemas Computacionais de Alto Desempenho, 2010)
This article proposes a model for resource discovery directed to ubiquitous computing with technologies for semantic processing aggregated to its architecture. The EXEHDA-SD contributes to increase the expressiveness of the representation and consultation for resources in a ubiquitous environment. The mechanism considers the dynamics in which resources enters or leaves the environment and pursue issues such as scalability and user preferences. The semantic processor and other components of the architecture of the mechanism are described as central contributions of the work.